1987
DOI: 10.1111/j.1559-1816.1987.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Social Support in Men with AIDS and ARC: Relationships with Distress and Hardiness1

Abstract: Previous research has suggested that social support may act as a buffer against stress or in other ways may affect physiological adjustment, health, longevity, and sense of well‐being. Perceptions of social support in persons newly diagnosed with Acquired Immune Deficiency Syndrome (AIDS) and AIDS‐related Complex (ARC) were examined as a part of an ongoing longitudinal study. Social support was examined in terms of emotionally‐sustaining and problem‐solving types of help, based on Gottlieb's content analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
1
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(53 citation statements)
references
References 55 publications
7
43
1
2
Order By: Relevance
“…For example, persons with HIV/AIDS report fewer feelings of helplessness and depression if friends or relatives are available to discuss emotional and illness-related issues (Ostrow et al, 1989;Zich & Temoshok, 1987). It should be noted that most of this research has focused on social support with gay men.…”
Section: Social Supportmentioning
confidence: 99%
“…For example, persons with HIV/AIDS report fewer feelings of helplessness and depression if friends or relatives are available to discuss emotional and illness-related issues (Ostrow et al, 1989;Zich & Temoshok, 1987). It should be noted that most of this research has focused on social support with gay men.…”
Section: Social Supportmentioning
confidence: 99%
“…Studies of social support and emotional well-being have demonstrated that people with AIDS report fewer feelings of depression and helplessness if they have close friends or relatives to talk to about emotional and illness-related problems (Ostrow et al, 1989;Zich and Temoshok, 1987).…”
Section: Social Supportmentioning
confidence: 99%
“…Tal reação poderia prejudicar um possível papel no tratamento de portadores do vírus da AIDS, conforme se demonstrou em um estudo feito em Nova Iorque com soropositivos, os quais, em função de se representarem contando com apoio social ou não, retardaram significativamente o desenvolvimento de sintomas da doença posteriormente (Zich & Temoshok, 1987). Houve manifestação verbal de cuidado social entre os HO que estudamos, que procurariam não contaminar outros caso se tornassem portadores do vírus.…”
Section: Discussionunclassified